Optimal match-up strategies in stochastic scheduling - Birge, John R.; Dempster, M.A.H. (Discrete Applied Mathematics, 1995)
Practical scheduling problems require the consideration of random events that may effect planned starting and completion times. In general, these problems are quite difficult to analyze. In a previous paper, general conditions were, however, developed for turnpike optimal strategies and the asymptotic optimality of strategies that match up with a turnpike strategy. In this paper, we present detailed examples of these general models, comparisons with deterministic approaches, and discuss implications for practical scheduling.